STRATEGI KOMUNIKASI PEMASARAN AGROWISATA PALOH NAGA DALAM MENINGKATKAN KUNJUNGAN WISATAWAN PASCA PANDEMI COVID-19 - Nurul Shahira Rizam; Nursapia Harahap (Jurnal Ilmiah Global Education, 2023)
The purpose of this study is to find out an overview of "Paloh Naga Agrotourism Marketing Communication Strategy in increasing tourist visits after the COVID-19 pandemic. The research method uses a qualitatively descriptive research approach. Data analysis uses data reduction, data presentation, then conclusions. The results showed that the marketing communication strategy in developing educational tourism objects of Paloh Naga Agrotourism uses the concept of marketing communication mix which is a support in increasing the number of visitors to Paloh Naga Agrotourism and is most relied on by managers, namely word-of-mouth and digital marketing or E-WOM (Electronic Word Of Mouth) such as Google, Facebook, Twitter,  Instagram even to Youtube. Furthermore, there are supporting and inhibiting factors in developing Paloh Naga Agrotourism objects. In this case, supporting factors and inhibiting factors are divided into two, namely, internal and external. Internal supporting factors are natural resources, human resources, financial resources, and strategic location. While the external supporting factor is the enthusiasm and full support of the community with the construction of Paloh Naga Agrotourism. The internal inhibiting factor is the lack of promotion intensity and cooperation. While the external inhibiting factor is the lack of support for print media and electronic media.